ZONATION AND DENSITY OF INTERTIDAL COMMUNITIES AT COASTAL AREA OF BATU HIJAU, SUMBAWA - Fredinan Yulianda; Muhamad Salamuddin Yusuf; Windy Prayogo (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
Characteristics of coastal tidal areas of Batu Hijau vary from sandy substrate type, sandy to rocky reef with a wide expanse of intertidal ranges from 100 meters to 350 meters. To find out zoning intertidal community,the observation conducted at five locations intertidal beach, each consisting of three zones: the high tide, middle tide and low tide. Living structure in tidal areas of coastal Batu Hijau, Sumbawa consists of the main communities and associated biota. The main intertidal community composed of coral, seagrass, algae, and other fauna, while the intertidal biota associated with tidal habitat consists of a group of molluscs, echinoderm, crustacean, worms and fish. Distribution of intertidal communities formed three zones consisting of (1) seagrass (21.3%) in the upper zone (high tide), (2) algae (35.5%) in the central zone (mid tide), and (3) coral (28.5%) and algae (42.5%) in the lower zone (low tide). The main groups of biota in the form of tidal zoning system consisting of two groups of molluscs (51.12%) in the upper zone, while the echinoderms that predominate in the central zone (36.96%) and lower (66.89%). No significant differences between the structure and composition of marine intertidal communities in September 2011 (rainy season) and April 2012 (dry season). Keywords: intertidal (tidal), percent cover, density, community, biota